2010
DOI: 10.3109/03093640903584993
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Prosthetic Fitting and Later Functional Outcome in Children and Young Adults with Unilateral Congenital Below-Elbow Deficiency

Abstract: The objective of this study was to evaluate whether prosthetic fitting before the age of one year is associated with better outcomes in children with unilateral congenital below-elbow deficiency compared to children fitted after the age of one. Twenty subjects aged 6-21 years were recruited (five prosthetic users and 15 non-users). The Child Amputee Prosthetics Project-Prosthesis Satisfactory Inventory (CAPP-PSI) and the Prosthetic Upper Extremity Functional Index (PUFI) were used to assess patient satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
2
39
2
Order By: Relevance
“…This is in accordance with the findings of a previous study in which functionality among children with ULRD was evaluated [29]. Adaptation to the prosthesis often encourages the users to increase their wearing time [29][30]. This may stimulate the clients to use their prostheses in daily activities and hence achieve better myoelectric control, which can explain the difference related to wearing pattern.…”
Section: Discussionsupporting
confidence: 77%
“…This is in accordance with the findings of a previous study in which functionality among children with ULRD was evaluated [29]. Adaptation to the prosthesis often encourages the users to increase their wearing time [29][30]. This may stimulate the clients to use their prostheses in daily activities and hence achieve better myoelectric control, which can explain the difference related to wearing pattern.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have been performed to evaluate functioning in daily life of children with UCBED with or without prosthesis [1,2,6,[15][16][17][18]. However, our study is the first with a longitudinal and observational design starting in infancy.…”
Section: Discussionmentioning
confidence: 98%
“…e l s e v i e r . c o m / l o c a t e / e a r l h u m d e v indicated that children with UCBED may show impaired adaptation of motor behaviour [6]. We therefore started a longitudinal observational multiple case study in order to explore how young children with UCBED use the affected limb during a standardized play session.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Wagner study (2007) on 489 upper limb amputee, data from 110 subject who reject prosthesis use, showed that "58% had been fitted befor age 1years of age and 18% had been fitted between 1 and 2 years of age" because of uncomfortability and not help to function. In another study Huizing (2010) concluded that prosthetic fittingt before 1 years age, leading to a longer use of prosthesis (more than four years), but does not improve motor behavior [16]. Some study showed that children in certain phases of the life (for example maturation) trend to reject of prosthesis [5,9,18].…”
Section: Early Fitting Of Prosthesismentioning
confidence: 99%